Loneliness beyond age. An intergenerational Project - Eiguren Munitis, Amaia; Berasategui Sancho, Naiara; Picaza Gorrotxategi, Maitane (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
For years it has been shown that it is necessary to promote spaces for intergenerational exchange in order to build more supportive and inclusive societies. Based on this framework, this article evaluates an intergenerational experience carried out in a university where students and older people share their views on loneliness through letters. The Iramuteq software was used to analyze the material collected (18 letters and 82 narratives). The results highlight the methodology itself as a new way of relating to each other that enables the exchange and mutual knowledge necessary in a segregated society.